Developing an Empathy Spectrum for Games. Issue 6 (September 2021) - Jerrett, Adam; Howell, Peter; Dansey, Neil
Games often encourage players to feel empathy for characters or scenarios by design. However, the term 'empathy' is often misunderstood and used in a variety of contexts as a substitute for feelings of sympathy, pity and compassion. This article defines a distinction between these similar terms and uses their definitions to describe how players emotionally engage with a game. This helps define an empathy spectrum, ranging from pity to compassion, that can be used to subjectively classify different games. To show the spectrum in use, the article discusses a variety of video games that can be placed at the spectrum's key points, before discussing how games might reach the spectrum's furthest point: compassion. The research hopes that modelling these abstract psychological concepts on this spectrum can help game designers, players and scholars better understand the range of emotional responses present in games.